1865-66 N.C. Sess. Laws 69-70, Priv. Laws, ch. 7, § 30. - (:unkn) unknown (General Publisher, 1866)
That the said board of aldermen shall have power to make from time to time, ordinances, rules and regulations concerning the firing of fire-arms, and all explosions in said city, the pace and speed at which horses may be driven or rode through the streets, the arrangements of stove-pipes in buildings, the mode in which fire shall be kept, or carried through the city, the manner in which powder and other explosive and inflammable substances may be kept and sold
--
Keywords: DISCHARGE; GUN POWDER STORAGE